Idioms in Croatian and German newspaper articles about the coronavirus - Pavić Pintarić, Anita (Slavia Centralis, 2022)
The coronavirus pandemic in 2020 led to a number of changes in people’s lifestyles and behaviour. These were the topics covered in newspaper articles in the period between March and June 2020, which created the corpus for this investigation. Newspaper articles focused on the fight against viruses, reactions to lockdown, the post-lockdown economy and how the EU and the world were coping with the crisis. The analysis in this paper is based on the Conventional Figurative Language Theory (CFLT) in order to investigate how these topics are represented by metaphorical idioms in a selected Croatian and German corpus. The research questions in this paper are as follows: In which topics related to coronavirus do idioms appear? What target concepts are expressed using idioms? What metaphors and source domains can be identified in idioms? Are there any similarities between Croatian and German?